Finite Element Analysis of Maxwell's Equations in Dispersive Lossy Bi-Isotropic Media (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, the time-dependent Maxwell's equations used to modeling wave propagation in dispersive lossy bi-isotropic media are investigated. Existence and uniqueness of the modeling equations are proved.Two fully discrete finite element schemes are proposed, and their practicalimplementation and stability are discussed.